Método exploratorio aplicando metalosato de magnesio y zinc (quelatos), en dos tipos de injertación en cacao (theobroma cacao l.) en patrones trinitarios y forasteros en la etapa de vivero - Vergara Álvarez, Jaime Alfredo (2017)
The present research was carried out in the Association of Nurseries "Sowing Future" located km 6½ of the Via Quevedo - El Empalme, between the months of April and July of 2016. Its objective was to evaluate the effect of Magnesium and Zinc Metalosate on development Of graft lateral barb and patch of cocoa (Theobroma cacao L.) in patterns CCN-51 and IMC-67. For the present study, a trifactorial arrangement was used as the first factor, and as a third factor (CCN-51 and IMC-67) as the second factor, zinc and magnesium as the second factor, grafting methods (lateral spike and patch) Of a completely randomized design (DCA), with 4 replicates, Tukey's test (P≤0.05), (p≤0.01) was used for the differences between the means. Agronomic variables were obtained at 30, 45, 60, days after grafting. Under the application of Zinc and Magnesium Metalosates (chelates) in the cocoa (Theobroma cacao L.) CCN-51 and IMC-67 patterns, it was evidenced that the zinc metalosate effect, in the trinitarian origin cocoa grafted seedlings CCN-51; Showed significant effects on the percentage of stuckness in the periods evaluated with 91.56% at 30 days, the behavior of the biostimulant was statistically differed which better the interaction obtained a greater response in graft size 14.11 cm, graft diameter 0.80 cm , Number of leaves 11.51 cm, leaf length 15.57 cm and average value leaf width 7.00 cm, showing good response at 60 days. The economic analysis presented the best benefit cost, treatment T1 with 4.61 dollars using zinc Metalosate by lateral graft pike.